Limit load analysis of strength undermatched welded T-joints under bending - ALEXANDROV, S.; KOÇAK, M. (Fatigue & fracture of engineering materials & structures, 2007)
ABSTRACT An increasing amount of laser beam welded T‐joints (e.g. skin‐stringer) of aluminium alloys are now in use in advanced fuselage applications designed as ‘integral structures’ for weight and cost savings. It is known that weld joints generally show lower strength (undermatching) than base metal in both laser beam and friction stir welded joints of 6xxx series Al‐alloys. Damage tolerance considerations in terms of the residual strength of such joints require limit load solutions to be used in engineering fitness‐for‐service (FFS) analysis. The paper, therefore, provides an upper bound limit load solution in closed form for welded T‐joints (idealized) with strength undermatching and subject to a bending moment. In addition to the necessary requirements of the upper bound theorem, the kinematically admissible velocity field chosen leads to a stress field, which satisfies the equilibrium equations and some stress boundary conditions in the plastic zone. This is an advantage of the solution and, therefore, it is expected that the upper bound obtained is close to the exact limit load of such joints.